Temperature-Dependent Effects of Cutaneous Bacteria on a Frog’s Tolerance of Fungal Infection - Robak, Matthew J.; Richards-Zawacki, Corinne L. (Frontiers in Microbiology, 2018)
Defense against pathogens is one of many benefits that bacteria provide to animal hosts. A clearer understanding of how changes in the environment affect the interactions between animals and their microbial benefactors is needed in order to predict the impact and dynamics of emerging animal diseases. Due to its dramatic effects on the physiology of animals and their pathogens, temperature may be a key variable modulating the level of protection that beneficial bacteria provide to their animal hosts. Here we investigate how temperature and the makeup of the skin microbial community impact the susceptibility of amphibian hosts to infection by Batrachochytrium dendrobatidis, one of two fungal pathogens known to cause the disease chytridiomycosis. To do this, we manipulated the skin bacterial communities of susceptible hosts, northern cricket frogs (Acris crepitans), prior to exposing these animals to Batrachochytrium dendrobatidis under two different ecologically relevant temperatures. Our manipulations included one treatment where antibiotics were used to reduce the skin bacterial community, one where the bacterial community was augmented with the antifungal bacterium, Stenotrophomonas maltophilia, and one in which the frog's skin bacterial community was left intact. We predicted that frogs with reduced skin bacterial communities would be more susceptible (i.e., less resistant to and/or tolerant of Bd infection), and frogs with skin bacterial communities augmented with the known antifungal bacterium would be less susceptible to Bd infection and chytridiomycosis. However, we also predicted that this interaction would be temperature dependent. We found a strong effect of temperature but not of skin microbial treatment on the probability and intensity of infection in Bd-exposed frogs. Whether temperature impacted survival, however, differed among our skin microbial treatment groups, with animals having more S. maltophilia on their skin surviving longer at 14 but not at 26 °C. Our results suggest that temperature was the predominant factor influencing Bd's ability to colonize the host (i.e., resistance) but that the composition of the cutaneous bacterial community was important in modulating the host's ability to survive (i.e., tolerate) a heavy Bd infection.